2018
DOI: 10.1007/s00706-018-2197-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of new amidrazone-derived hydrazides as a potential anti-inflammatory agents

Abstract: The series of new hydrazide derivatives were synthesized in reactions of N3-substituted amidrazones with cyclic anhydrides as potential anti-inflammatory and antibacterial agents. The compounds were characterized by 1H-13C two-dimensional NMR techniques, which revealed the presence of two tautomeric forms in DMSO-d6 solutions, while the molecular structure of one species was confirmed by single-crystal X-ray diffraction. The anti-inflammatory effects of hydrazides on peripheral blood mononuclear cells were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Compound 57 , at a concentration of 50 µg/mL, showed no toxicity but strongly inhibited the proliferation of PBMC activated by anti-CD3 antibodies or phytohaemagglutinin by 90–99%, and the observed effects were comparable to or stronger than those of ibuprofen. The mechanism of action of derivative 57 is cell cycle arrest at the G1 phase [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compound 57 , at a concentration of 50 µg/mL, showed no toxicity but strongly inhibited the proliferation of PBMC activated by anti-CD3 antibodies or phytohaemagglutinin by 90–99%, and the observed effects were comparable to or stronger than those of ibuprofen. The mechanism of action of derivative 57 is cell cycle arrest at the G1 phase [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, PBMC are widely used as a physiological model for immunological research of parasitic infections, such as those caused by Toxoplasma gondii and others [ 43 ]. PBMC are routinely isolated from blood samples (as we describe previously in [ 44 ]) and then used in several different tests to determine the toxicity, anti-proliferative activity and anti-inflammatory activity of studied compounds. We used the cytometric method to evaluate the proliferation response to phytohemagglutinin (PHA) and immunoezymatic tests to verify the levels of proinflammatory cytokines after lipopolysaccharide (LPS) stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-five examined chemical compounds were obtained in the reaction of N 3substituted amidrazones with cyclic anhydrides, following methods described previously [12][13][14]. Generally, they belong to three groups depending on chemical structure (linear, 1,2,4-triazole derivatives, and cyclic imides, as shown in Figure 1).…”
Section: Predicted and Potential Predictive Variables In The Modelmentioning
confidence: 99%
“…Previous studies have demonstrated that unsubstituted amidrazones and their chloride or bromide salts exhibit good antibacterial activity. Due to our experience in the synthesis of N 3 -substituted amidrazone derivatives, compounds such as acyclic derivatives [12], 1,2,4-triazole derivatives [13] and cyclic imides [14] were selected for this research. In this study, we attempted to determine the influence of the R1 and R2 substituents and other structural factors of new N 3 -amidrazone derivatives on their antibacterial against selected strains of Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%